Thrombocytopenia and its Relationship with Bleeding Manifestations in Dengue Patients-A Tertiary Care Hospital Experience - Shabir, Mahtab; Nisar, Shazia; Urooj, Zobia; Sohail, Mohina; Khan, Muhammad Shahid; Khan, Danish Hassan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore the extent of bleeding among three different groups of patients based on their blood platelet count and identify the frequency of specific types of bleeding manifestations among the study groups.Study Design: Comparative prospective study.Place and Duration of Study: Pak-Emirates Military Hospital, (PEMH) Rawalpindi Pakistan, from Jul to Dec 2019.Methodology: One hundred patients hospitalized with dengue fever and platelet count of less than 100,000 per microliter of blood were enrolled in the study. They were divided into three groups based on platelet count, i.e., 50,000 (Group-3) per microliter of blood and observed for different types of bleeds and were also categorized as no bleed, single-site bleed and multiple-site bleed.Results: Group comparisons revealed that no patient from Group-1 versus 3(10.3%), patients from Group-2 whereas 11(19.3%) patients from Group-3 experienced single site bleed (p=0.05). In addition, patients belonging to Group-1 experienced significantly more petechiae as compared to Groups 2 and 3 (92.8% vs 65.5% vs 19.2%, p